Silver-quercetin-loaded honeycomb-like Ti-based interface combats infection-triggered excessive inflammation via specific bactericidal and macrophage reprogramming - Ning Yang; Ting Wu; Meng Li; Xianli Hu; Ruixiang Ma; Wei Jiang; Zheng Su; Rong Yang; Chen Zhu (Bioactive Materials)
Excessive inflammation caused by bacterial infection is the primary cause of implant failure. Antibiotic treatment often fails to prevent peri-implant infection and may induce unexpected drug resistance. Herein, a non-antibiotic strategy based on the synergy of silver ion release and macrophage reprogramming is proposed for preventing infection and bacteria-induced inflammation suppression by the organic-inorganic hybridization of silver nanoparticle (AgNP) and quercetin (Que) into a polydopamine (PDA)-based coating on the 3D framework of porous titanium (SQPdFT). Once the planktonic bacteria (e.g., Escherichia coli, Staphylococcus aureus) reach the surface of SQPdFT, released Que disrupts the bacterial membrane. Then, AgNP can penetrate the invading bacterium and kill them, which further inhibits the biofilm formation. Simultaneously, released Que can regulate macrophage polarization homeostasis via the peroxisome proliferators-activated receptors gamma (PPARγ)-mediated nuclear factor kappa-B (NF-κB) pathway, thereby terminating excessive inflammatory responses. These advantages facilitate the adhesion and osteogenic differentiation of bone marrow-derived mesenchymal stem cells (BMSCs), concomitantly suppressing osteoclast maturation, and eventually conferring superior mechanical stability to SQPdFT within the medullary cavity. In summary, owing to its excellent antibacterial effect, immune remodeling function, and pro-osteointegration ability, SQPdFT is a promising protective coating for titanium-based implants used in orthopedic replacement surgery.